Mark of the Beast. (23rd March 2022) - Sprankle, Eric; Hensel, Zane; Jennings, Todd; Lyng, Tayler
Abstract : Modern Satanism is an oft-misunderstood and stigmatized minority religion that has largely been viewed by mental health professionals through a lens of deviance. Understanding Satanists' experiences with this stigmatized identity is absent in the current psychological literature. Conceptualizing Satanism within the minority stress and rejection-identification models, a nonrandom sample of 1, 272 self-identified Satanists were surveyed about their strength of identity, anticipated discrimination, and depressive symptoms. Results indicated that aspects of Satanist identity (centrality and in-group ties) positively correlated with anticipated discrimination, and other aspects (in-group ties and in-group affect) negatively correlated with depressive symptoms. Additionally, in-group ties moderated the relationship between anticipated discrimination and depressive symptoms, suggesting that Satanists who have social support from other Satanists are less affected by the depressive repercussions of anticipated discrimination. Implications for mental health professionals treating Satanists presenting with religious minority stressors and depressive symptoms are discussed.